2020
DOI: 10.3389/fchem.2020.00569
|View full text |Cite
|
Sign up to set email alerts
|

Monosaccharides Dehydration Assisted by Formation of Borate Esters of α-Hydroxyacids in Choline Chloride-Based Low Melting Mixtures

Abstract: The synthesis of 5-hydroxymethylfurfural (5-HMF) and 2-furfural (2-F) by hexoses and pentoses dehydration is considered as a promising path to produce materials from renewable resources. Low-transition-temperature mixtures (LTTMs) enable selective (>80%) dehydration of ketoses to furanic derivatives at moderate temperature (<100 • C). However, aldoses dehydration generally requires higher temperatures and an isomerization catalyst. Chromium trichloride has been reported as one of the most efficient catalyst bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Under strong acidity provided by HCl or H 2 SO 4 , sodium tetraborate is decomposed to boric acid and the corresponding sodium salt. Boric acid catalyses the formation of HMF; however, it also enables polymerization side reactions, as mentioned by the Istasse et al [ 31 ], especially in the presence of salts as demonstrated by Hansen et al [ 36 ]. Apart from the boron species, another crucial factor for the selective synthesis of HMF is pH.…”
Section: Resultsmentioning
confidence: 99%
“…Under strong acidity provided by HCl or H 2 SO 4 , sodium tetraborate is decomposed to boric acid and the corresponding sodium salt. Boric acid catalyses the formation of HMF; however, it also enables polymerization side reactions, as mentioned by the Istasse et al [ 31 ], especially in the presence of salts as demonstrated by Hansen et al [ 36 ]. Apart from the boron species, another crucial factor for the selective synthesis of HMF is pH.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the newly generated six-membered ring of dihydrofructosazine [2,5bis(d-arabino-tetrahydroxybutyl)dihydropyrazine] intermediate I may break the two arylborate esters from aggregated complexes because of steric effect and better water solubility. A subsequent chem-selective dehydration directed by arylboronic ester 42 occurred and this arylboronic acid may dissociate to be a free acid form or transfer to D-glucosamine raw material regenerating a glucosamine arylborate ester; Reaction with phenylboronic acid pinacol ester (Entry 10, Table 3) gave a comparable yield of DOF to reaction with the same amount of phenylboronic acid, also indicating the presence of fast boron transfer in the system. Then a followed isomerization generated arylboronic acid protected deoxyfructosazine intermediate II.…”
Section: Proposed Boron Transfer Mechanismmentioning
confidence: 98%
“…Then the newly generated six-membered ring of dihydrofructosazine [2,5-bis(d-arabinotetrahydroxybutyl)dihydropyrazine] intermediate I may break the two arylborate esters from aggregated complexes because of steric effect. A subsequent chem-selective dehydration directed by arylboronic ester 40 occurred and this arylboronic acid may dissociate to be a free acid form or transfer to D-glucosamine raw material regenerating a glucosamine arylborate ester; then a followed isomerization generated arylboronic acid protected deoxyfructosazine intermediate II. Because of better water-soluble pyrazine moiety and seven hydroxyls, arylboronic acid protected deoxyfructosazine would have a stronger hydrate effect in water and tend to stay in bulk water; that could favor equilibration to an arylborate ester via direct boron transfer or dissociation to a free arylboronic acid followed with a chelation to glucosamine, completing a catalytic cycle.…”
Section: Proposed Boron Transfer Mechanismmentioning
confidence: 99%
“…Because of better water-soluble pyrazine moiety and seven hydroxyls, arylboronic acid protected deoxyfructosazine would have a stronger hydrate effect in water and tend to stay in bulk water; that could favor equilibration to an arylborate ester via direct boron transfer or dissociation to a free arylboronic acid followed with a chelation to glucosamine, completing a catalytic cycle. The existence of arylboronic acid is a key to push dihydrofructosazine intermediate to dehydration 40 (to deoxyfructosazine) rather than dehydrogenation (to fructosazine).…”
Section: Proposed Boron Transfer Mechanismmentioning
confidence: 99%